ANTIKOM Inventory of documents - ANTIKOM (ARCA, 2018)
The Anti-Communist Action Committee; Delivered church commission information against communism; Pamphlets
COVERAGE 7 pamphlets; 0.10 metre
Keywords: ANTIKOM; Anti-Communism; South Africa